2014
DOI: 10.3389/fnhum.2014.00603
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual review on action-perception coupling in the musicians’ brain: what is it good for?

Abstract: Experience with a sensorimotor task, such as practicing a piano piece, leads to strong coupling of sensory (visual or auditory) and motor cortices. Here we review behavioral and neurophysiological (M/EEG, TMS and fMRI) research exploring this topic using the brain of musicians as a model system. Our review focuses on a recent body of evidence suggesting that this form of coupling might have (at least) two cognitive functions. First, it leads to the generation of equivalent predictions (concerning both when and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 103 publications
6
102
0
1
Order By: Relevance
“…Conceivably, long-term musical rehearsal and production might also act to improve the prediction of both when and what auditory and visual events are likely to occur as it does in the auditory-motor system (Novembre and Keller 2014;van Vugt and Tillmann 2014). As conceived by Novembre and Keller (2014), experiencedependent coupling of perception and actions (or other percepts) might help "scaffold the human ability to represent complex (structured) actions and entrain to multiple agents (Novembre and Keller 2014;p.1)." Structured actions and multiagent entrainment is essential in joint musical tasks such as ensemble performance.…”
Section: Domain-general Benefits Of Music-related Plasticitymentioning
confidence: 96%
“…Conceivably, long-term musical rehearsal and production might also act to improve the prediction of both when and what auditory and visual events are likely to occur as it does in the auditory-motor system (Novembre and Keller 2014;van Vugt and Tillmann 2014). As conceived by Novembre and Keller (2014), experiencedependent coupling of perception and actions (or other percepts) might help "scaffold the human ability to represent complex (structured) actions and entrain to multiple agents (Novembre and Keller 2014;p.1)." Structured actions and multiagent entrainment is essential in joint musical tasks such as ensemble performance.…”
Section: Domain-general Benefits Of Music-related Plasticitymentioning
confidence: 96%
“…It has been suggested that musicians exhibit distinct auditory (42,43), verbal (44), and broad cognitive (45) abilities and/or systems. In particular, musical training, whether singing or playing an instrument, requires developing perception-action coordination, which may promote unusually strong connections between perception and action systems in the brain (46,47). Storage and retrieval of musical melodies may be subserved by auditory-motor pathways including the premotor area (48).…”
Section: Discussionmentioning
confidence: 99%
“…According to these explanations, sounds are successfully perceived and interacted with by internally simulating the likely actions that produced them in the motor cortex (see [91] for a recent review in relation to music). Successful interaction from an agent therefore depends on learnt mappings between external events and internal representations of our own (and others) sound-actions effects.…”
Section: Bringing Sounds Into Usementioning
confidence: 99%